2021
DOI: 10.1177/10870547211044217
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder as a Risk Factor for COVID-19 Infection

Abstract: Objective: To postulate that ADHD is a potential risk factor for COVID-19 infection; to evaluate the COVID-19 risk factor on drug-treated ADHD subjects. Methods: A retrospective chart review was performed on ADHD subjects aged 6 to 18 years in Israel, who had undergone at least one COVID-19 test during the study period. Results: Of the 64,409 subjects included in the study, 6,207 (9.64%) had at least one positive COVID-19 test result, 13,300 (20.65%) were diagnosed with ADHD, and of whom 1,751 (13%) had purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
(17 reference statements)
4
12
1
Order By: Relevance
“…We found that no demographic or clinical factors significantly impacted COVID-19 infection status. COVID-19 positive test status did not differ between treated and untreated ADHD patients whereas this finding did not corroborate with two studies that demonstrated that treated ADHD subjects had a lower risk for COVID-19 than untreated ADHD ( 2 , 28 ). The discrepancy could be explained by the different study populations.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…We found that no demographic or clinical factors significantly impacted COVID-19 infection status. COVID-19 positive test status did not differ between treated and untreated ADHD patients whereas this finding did not corroborate with two studies that demonstrated that treated ADHD subjects had a lower risk for COVID-19 than untreated ADHD ( 2 , 28 ). The discrepancy could be explained by the different study populations.…”
Section: Discussioncontrasting
confidence: 81%
“…The discrepancy could be explained by the different study populations. The first study included both children and adults and the latter study included only children ( 28 ). Another explanation could be different presentations of ADHD during childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD patients, particularly those not treated for ADHD, were more susceptible to COVID-19 infection than those without ADHD and those who received ADHD pharmacotherapy ( Merzon et al, 2021 ). Similar results of increased risk for infection were also reported in untreated pediatric ADHD patients from Israel when compared with medically-treated children ( Cohen et al, 2022 ), and in adult ADHD patients in the US when compared with those without a diagnosed mental disorder (adjusted OR = 5.82, 95% CI [5.46, 6.20], p < .001) ( Wang et al, 2021 ). In a subsequent study (1,870 COVID patients), Merzon et al (2022) reported that ADHD was associated with more severe symptoms of COVID-19 (OR 1.81, 95% CI [1.29, 2.52], p < .05) and referral for hospitalization (OR 1.93, 95% CI [1.06, 3.51], p = .03).…”
Section: Introductionsupporting
confidence: 70%
“…Untreated subjects with ADHD seem to constitute a risk group for COVID-19 infection with poor outcomes. 15 17 In our study, we found that older adolescents with ADHD, aged 16-17 years, were more likely to be vaccinated. The ultra-orthodox Jewish and Arab adolescents in the ADHD group were far less likely to be vaccinated (22.9% and 34.6%, respectively), compared to the adolescents with ADHD in the general population (60.5%).…”
Section: Discussionmentioning
confidence: 48%
“… 15 , 16 ADHD was also found to be associated with more severe COVID-19 symptoms and hospitalizations. 17 However, in a US study, recovery rates were found to rise with the prevalence of ADHD 18 suggesting that ADHD may have a protective role against severe COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 95%